2016
DOI: 10.1371/journal.pone.0162941
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Calculating Student-Centered Value in Education – A Link between Quality, Efficiency, and the Learning Experience in the Health Professions

Abstract: Health professional education is experiencing a cultural shift towards student-centered education. Although we are now challenging our traditional training methods, our methods for evaluating the impact of the training on the learner remains largely unchanged. What is not typically measured is student-centered value; whether it was ‘worth’ what the learner paid. The primary aim of this study was to apply a method of calculating student-centered value, applied to the context of a change in teaching methods with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(17 reference statements)
0
7
0
2
Order By: Relevance
“…As Gunyou (2015) stresses, the FL modality may be particularly cost-effective when compared with the high costs of the traditional large bricks and mortar highereducational structures. This greater benefit takes the form of value to students as measured by course fees, the value of the learning approach and student satisfaction (Nicklen et al, 2016), and considerations about quality improvement (Rotellar & Cain, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…As Gunyou (2015) stresses, the FL modality may be particularly cost-effective when compared with the high costs of the traditional large bricks and mortar highereducational structures. This greater benefit takes the form of value to students as measured by course fees, the value of the learning approach and student satisfaction (Nicklen et al, 2016), and considerations about quality improvement (Rotellar & Cain, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, until economic evaluations of theoretically and pedagogically sound OOCs are conducted, any claims toward these aspirations lack credibility. The combination of making open courses available to vulnerable learner populations, such as those in low income countries, along with fees for certification in the absence of high quality educational evidence of student outcomes and learning experience, further raises concerns of moral and professional accountability [75].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies [14,15,17,21,24,25,27,28,[34][35][36][37]41,46,47,51] compared eLearning costs to those of face-to-face learning or other types of learning (Table 3). These comparative studies offered more evidence that the use of eLearning demonstrated cost efficiencies than did the studies in the previous group, which provided no comparative data.…”
Section: Studies Describing Elearning Costs With a Comparatormentioning
confidence: 99%